2014
DOI: 10.1007/s12192-013-0487-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of novel ER-based hsp90 gene in the red flour beetle, Tribolium castaneum

Abstract: Heat-shock protein 90 (HSP90) is a highly conserved molecular chaperone found in all species except for Archaea, which is required not only for stress tolerance but also for normal development. Recently, it was reported that HSP83, one member of the cytosolic HSP90 family, contributes to oogenesis and responds to heat resistance in Tribolium castaneum. Here, a novel ER-based HSP90 gene, Tchsp90, has been identified in T. castaneum. Phylogenetic analysis showed that hsp90s and hsp83s evolved separately from a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 52 publications
2
29
0
Order By: Relevance
“…As T. castaneum is basically living in the warm cereal storage place and without diapause, Tchsp21.8b was in response to heat but exhibited insensitiveness to cold stress. This phenotype was also existed in ER‐based Tchsp90 and Tchsp18.3 , both of which were only upregulated by heat stress (Xie et al., ; Zhang, Gu et al., ), indicating that the behaviour would make a similar induction of other hsps in T. castaneum .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…As T. castaneum is basically living in the warm cereal storage place and without diapause, Tchsp21.8b was in response to heat but exhibited insensitiveness to cold stress. This phenotype was also existed in ER‐based Tchsp90 and Tchsp18.3 , both of which were only upregulated by heat stress (Xie et al., ; Zhang, Gu et al., ), indicating that the behaviour would make a similar induction of other hsps in T. castaneum .…”
Section: Discussionmentioning
confidence: 92%
“…This result suggested that the orthologous shsp also could be in response of the oxidative stress caused by UV exposure, similar with hsp70 and hsp90 . Likewise, the orthologous shsp showed analogous expression profiles with hsp70 and hsp90 under starvation stress (Shim, Kim, & Lee, ; Zhang, Gu et al., ). As both of hsp70 level and hsp90 level decreased greatly when the insect larvae were starved for days, Tchsp21.8b was also downregulated by starvation stress for 3 days, with a decreased degree of 20.8%–41.8% compared to the control (Figure b).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Additionally, they have a significant role in the protection and maintenance of many fundamental cellular functions (Nadeau et al ., ). There are several studies on Hsps characterization and expression in response to stress conditions in T. castaneum (Xu et al ., ; Holmstrup et al ., ; Schinko et al ., ; Zhang et al ., ). Sang et al .…”
Section: Introductionmentioning
confidence: 99%